A hybrid swarm algorithm and its application in vehicle route guide system on wireless network. (5th September 2019) - Xin, Qi; Chenghao, Han
In this paper, a hybrid optimisation algorithm for the vehicle route guide system on wireless network is presented. Applying the wireless sensor network technology to intelligent transportation systems has become a research hotspot in recent years. Research on the shortest path algorithms and improving vehicle route guide system has been the core of the study on the intelligent transport systems. The goal of our approach is to reduce the computing time and get better solutions. By a thorough analysis of several existing optimal routing choice algorithms, we proposed an optimal routing choice algorithm based on Artificial Fish Swarm Algorithm (AFSA). Our simulations show that the speed of convergence of the improved algorithm is enhanced greatly compared with other optimal choice algorithms, and the new algorithm obtained a better result. The results show that the improved algorithm can apply to intelligent transport systems.